Bibliometric and Visualized Analyses of Research Studies on Different Analgesics in the Treatment of Orthopedic Postoperative Pain - Yunzhong Cheng; Honghao Yang; Li Guan; Yong Hai; Aixing Pan (Pain Research and Management)
Background. Pain following orthopedic surgery has always been a critical issue, which caused great distress to the patients. Analgesics in the treatment of postoperative pain following orthopedic surgery have aroused great attention from scholars, and numerous studies have been published in recent years. Bibliometrics could assist scholars in understanding the scope of research topics better, identifying research focuses and key literature, and analyzing the development and trend of analgesics in the treatment of postoperative pain following orthopedic surgery. Methods. Literature data were retrieved from the Science Citation Index Expanded (SCI-E) of Web of Science (WOS) Core collection database. The articles from 1992 to December 2021 on analgesics in the treatment of postoperative pain following orthopedic surgery were recruited. The citation reports including the publication numbers, h-index, total citations, and average citations in terms of authors, organizations, and countries were obtained. Top 20 research directions, funds, and journals with the most publications were charted. The co-authorship relations in the analysis units of authors, organizations, and countries were analyzed by the online bibliometric tool and VOSviewer software. The author’s keywords co-occurrence overlay map was visualized by the VOSviewer software. Results. A total of 406 articles were retrieved from 1992 to December 4th, 2021, with 11,655 times cited, average citations of 28.57 per item, and an h-index of 55. The most high-yield publication year, authors, organizations, countries, research directions, funds, and journals were 2020 (n = 887), Ilfeld BM from University of California San Diego (n = 7), University of California System (n = 21), the USA (n = 178), Anesthesiology (n = 161), National Institutes of Health (NIH), USA, and United States Department of Health Human Services (n = 12), and Anesthesia and Analgesia (n = 29), respectively. Similarly, co-authoring analysis of publications regarding on different analgesics showed that the authors and countries with the most co-authorship strength were Carr Daniel B (total link strength = 6) and the USA (total link strength = 30), respectively. The highest occurrence keywords were “postoperative pain” with 135 occurrences (total link strength = 784). The future research hotspots might be “acute pain,” “outcomes,” “oxycodone,” “total hip,” “replacement,” and “United States.” Conclusion. Analgesics in the treatment of postoperative pain following orthopedic surgery can be observed in this study by employing the online bibliometric tool and VOSviewer software, which established the relationship between the units of analysis. It can provide a meaningful resource with detailed information for orthopedic surgeons who would like to understand the trend in this field better. They can also benefit from the emphasis on citation count to carry out high-level research in the future.